The Use of Satirical Expression in Gila Lu Ndro! Film - Nurlian, Ramiz Naufal; Nuryanti, Dewi (ESENSI LINGUA, 2021)
This research is aimed to analyze the satirical expression in the GILA LU NDRO! film directed by Herwin Novianto. It is to identify the satirical expression that occur in the film in terms of explaining the purpose, the reason, and, types of using satirical expression by characters. The writers use theory Greenberg, Simpson, Charles, Greek, Catullus, and Marthial. This research applies qualitative method. The result of this research shows social issue that develop in society. The character, in the film has a character who build and provide the message. The plot, this film gives sequence from the introduction, the conflict and the result of the conflict itself. The last, the effects of this research give a positive effect to everyone. The writers also find the moral values in this film such as morality, humanity, attitude, religion, and, politic.